Voyager Smurf and the Magic Whistle - Wan, Ruth, 1976- (Singapore : WS Education, 2026)
"Come on a Smurf adventure with us! Enjoy reading while having fun with the Smurfs. There's always so much to learn and discover with these lovable characters that everyone can relate to! Voyager Smurf sets off for a great adventure, but things don't go as planned when his magic whistle falls into the wrong hands!"--
Keywords: Smurfs (Fictitious characters) -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction; Picture books